Method for preparing composite photocatalyst through resource utilization of magnesium slag or waste liquid

Through the pretreatment of magnesium slag or waste liquid and hydrothermal reaction between tin tetrachloride and urea, an efficient composite photocatalyst is prepared, which solves the problems of resource utilization of magnesium slag and poor performance of SnO2 catalysts, and realizes the atmosphere and water bodies Effective removal of pollutants, simple process and low cost.

CN119281316APending Publication Date: 2025-01-10CHONGQING INST OF GREEN & INTELLIGENT TECH CHINESE ACAD OF SCI +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411416716.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Magnesium slag and waste liquid have not been effectively utilized in resource utilization, and the existing SnO2 photocatalysts have low catalytic efficiency, poor stability and difficult to recover, and lack cheap raw materials and simple operating processes.

Method used

The magnesium salt solution is obtained by pretreating the magnesium slag or waste liquid, and hydrothermal reaction with the tin tetrachloride solution and urea solution to prepare a composite photocatalyst. The specific steps include grinding of magnesium slag, leaching of acid solution, and water treatment of ammonia. , precipitation adjustment, mix uniformly and hydrothermal reaction.

Benefits of technology

Resource utilization of magnesium slag or waste liquid is realized, and efficient composite photocatalysts are prepared, which can effectively remove atmospheric and water pollutants, such as toluene, ammonia nitrogen, COD, etc., and the process is simple, the cost is low, the catalyst stability and recycling are used. The effect is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119281316A_ABST
    Figure CN119281316A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a composite photocatalyst by resource utilization of magnesium slag or waste liquid, which comprises the following steps of: pretreating magnesium slag or waste liquid serving as a raw material to obtain a magnesium salt solution; and uniformly mixing a magnesium salt solution with a tin tetrachloride solution and a urea solution to obtain a mixed solution, carrying out a hydrothermal reaction, and carrying out post-treatment. The composite photocatalyst is a specific amount of magnesium-doped tin dioxide material and can be directly used for degradation of VOCs (Volatile Organic Compounds). According to the method, resource utilization of the magnesium slag or the waste liquid is realized, and the method is environment-friendly and has a good removal effect on typical environmental pollutant methylbenzene. The composite photocatalyst is prepared by adopting a hydrothermal method, the preparation process is simple, the production cost is low, and the operation is convenient.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of solid waste resource utilization, and provides a method for preparing a composite photocatalyst by resource utilization of magnesium slag or waste liquid. Background Art

[0002] Magnesium and its compounds are widely used in modern industry and life, mainly in alloy materials, biomedical materials, environmental protection energy, chemical and pharmaceutical industries. With the continuous improvement of industrial technology, the magnesium mining industry has developed rapidly, and the demand for magnesium resources has also increased, resulting in the increasing problem of magnesium tailings resource hoarding. According to statistics, the production of 1 ton of metallic magnesium consumes more than 10 tons of dolomite, and in actual production, one ton of magnesium produces 6-7 tons of reduction slag. In the long run, magnesium slag, as a waste in the magnesium production process, cannot be comprehensively utilized, which occupies a large amount of land resources, causing serious environmental pollution, and also causing a large amount of resource waste. Therefore, it is urgent to solve the comprehensive utilization of magnesium slag.

[0003] Scholars have conducted extensive research on the magnesium resource utilization of magnesium slag (waste liquid).

[0004] Patent CN 109867463 B utilizes magnesium resources in the hydrometallurgical zinc smelting process. Magnesium fluoride seeds and zinc fluoride are added to a magnesium-containing zinc sulfate solution to obtain a coarse-grained magnesium fluoride precipitate, and liquid-solid separation is performed; concentrated sulfuric acid is added to the magnesium fluoride precipitate for heating reaction to obtain hydrogen fluoride gas and magnesium sulfate; hydrogen fluoride is passed into a container containing zinc oxide dust to obtain zinc fluoride; a catalyst and an atmosphere regulator are added to magnesium sulfate and heated to decompose to obtain magnesium oxide; magnesium sulfate, an organic admixture, an inorganic admixture, a reinforcing agent, and short fibers are added to the magnesium oxide, and the mixture is evenly mixed to obtain magnesium oxysulfide cement.

[0005] Patent application CN 117023612 A discloses a method for resource utilization of magnesium-containing wastewater generated by nickel-cobalt hydrometallurgy. The method uses magnesium-containing waste liquid in the nickel-cobalt hydrometallurgy process as a raw material, reacts with liquid alkali to prepare magnesium hydroxide as a flame retardant, and comprises the following steps: the magnesium-containing waste liquid and the liquid alkali are added to a reactor in parallel, the precipitation pH value is controlled to carry out a precipitation reaction, and the magnesium hydroxide precipitate enters an aging kettle for aging; then the aged material is concentrated and filtered, the filter cake is washed with deionized water until the conductivity of the filtrate is below 50 μS, and the magnesium hydroxide product is obtained after drying, which is used as a flame retardant.

[0006] At present, the research on the application of magnesium slag (waste liquid) is mainly focused on cement concrete, building materials and flame retardant materials, and there has been no research on the resource utilization of magnesium-containing slag (waste liquid) to prepare new catalysts. Therefore, it is necessary to explore cheaper raw materials or simpler operating processes to meet the resource utilization of magnesium slag (waste liquid).

[0007] SnO2 is an n-type semiconductor. It has excellent electronic and optical properties and is widely used in gas sensors, photochemistry, and photodetectors. In the field of photocatalysis, compared with the commercial material TiO2, SnO2 has a stronger valence band and stronger oxidation ability, and is expected to oxidize pollutants more thoroughly. However, the existing prepared SnO2 photocatalysts have the disadvantages of low catalytic efficiency, poor stability, and difficulty in recycling. Summary of the invention

[0008] In view of this, the purpose of the present invention is to provide a method for preparing a composite photocatalyst by resource utilization of magnesium slag or waste liquid, aiming to solve the problems of resource utilization of magnesium slag or waste liquid and poor photocatalytic performance of SnO2.

[0009] To achieve the above object, the present invention provides the following technical solutions:

[0010] The present invention provides a method for preparing a composite photocatalyst by resource utilization of magnesium slag or waste liquid, and the specific steps are as follows:

[0011] S1. Pretreating the magnesium slag or waste liquid to obtain a magnesium salt solution;

[0012] S2. The magnesium salt solution is mixed evenly with the tin tetrachloride solution and the urea solution to obtain a mixed solution, so that the molar ratio of the total molar amount of magnesium ions and tin ions to urea is 1:2-4, and a hydrothermal reaction is performed and post-treated to obtain the composite photocatalyst.

[0013] Preferably, in step S1, the pretreatment method of the magnesium slag is as follows: the magnesium slag is ground to less than 150 μm, dried at 105° C. to constant weight to obtain slag powder, and then the slag powder is leached with a first acid solution for 24 hours, filtered to obtain a leachate containing magnesium sulfate, and then a 28% ammonia solution is added to the leachate, stirred, filtered, and a filter residue containing Mg(OH)2 is obtained, and finally a second acid solution is added dropwise to the filter residue until the pH is 4-6 and the precipitate disappears, and the magnesium ion concentration is adjusted.

[0014] Further preferably, the acid solution is selected from hydrochloric acid solution, sulfuric acid solution or nitric acid solution.

[0015] Further preferably, the dosage ratio of slag powder, the first acid solution and the ammonia solution is 50g:150mL:300mL, and the first acid solution and the second acid solution are respectively a 20% by mass concentration sulfuric acid solution and a 15% by mass concentration nitric acid solution.

[0016] More preferably, the magnesium ion concentration is adjusted to 0.5 mol / L.

[0017] Preferably, in step S1, the main component of the waste liquid is Mg 2+The corresponding pretreatment method is concentration or dilution with distilled water to adjust the magnesium ion concentration.

[0018] Further preferably, the waste liquid further comprises: K + 、Na + 、NO3 - 、Cl-、SO4 2- wait.

[0019] Preferably, in step S2, the molar ratio of the total molar amount of magnesium ions and tin ions to urea is 1:3.

[0020] Preferably, in step S2, the molar ratio of magnesium ions to tin ions is 1 to 4:1, more preferably 2:1.

[0021] Preferably, in step S2, the magnesium ion concentration in the magnesium salt solution is 0.5 mol / L, the concentrations of the tin tetrachloride solution and the urea solution are 0.5 mol / L and 3 mol / L, respectively, and the volume ratio of the magnesium salt solution, the tin tetrachloride solution, and the urea solution is 4.8-19.2:19.2-4.8:12.

[0022] More preferably, the volume ratio of the magnesium salt solution, the tin tetrachloride solution and the urea solution is 12-19.2:12-4.8:12, and more preferably 4:2:3.

[0023] Preferably, in step S2, stirring is performed for 10 minutes to achieve uniform mixing.

[0024] Preferably, in step S2, the process conditions of the hydrothermal reaction are: hydrothermal reaction at 120° C. for 12 hours.

[0025] Preferably, in step S2, the post-treatment includes: washing with distilled water and centrifuging for 3 times, washing with 95% ethanol solution by volume and centrifuging once, drying at 60° C. for 12 hours, and grinding.

[0026] A composite photocatalyst is prepared by the above method.

[0027] The application of the aforementioned composite photocatalyst in the removal of atmospheric pollutants and water pollutants.

[0028] Preferably, the air pollutants include, but are not limited to: toluene, formaldehyde, benzene, and xylene, and more preferably toluene.

[0029] Preferably, the water pollutants include but are not limited to: organic pollutants, ammonia nitrogen, humic acid, and esters.

[0030] The beneficial effects of the present invention are:

[0031] The present invention uses magnesium slag or waste liquid as raw materials, performs pretreatment to obtain a magnesium salt solution; then the magnesium salt solution is evenly mixed with a tin tetrachloride solution and a urea solution to obtain a mixed solution, and then subjected to hydrothermal reaction and post-treatment to obtain a composite photocatalyst. The composite photocatalyst is a tin dioxide material doped with a specific amount of magnesium, which can be directly used for the degradation of atmospheric pollutants VOCs and water pollutants. The present invention realizes the resource utilization of magnesium slag or waste liquid, is environmentally friendly, and has a good removal effect on typical environmental pollutants such as toluene, ammonia nitrogen, and CODD. The present invention adopts a hydrothermal method to prepare the composite photocatalyst, which has a simple preparation process, low production cost, and is easy to operate.

[0032] The composite photocatalyst has the effect of removing air pollutants and water pollutants, such as toluene (C7H8), formaldehyde (HCHO), benzene (C6H7), xylene (C8H 10 ), ammonia nitrogen, COD, humic acid, esters, etc. have removal effects. In the embodiments, toluene, ammonia nitrogen and COD are taken as examples.

[0033] Other advantages, objectives and features of the present invention will be described in the following description to some extent, and to some extent, will be obvious to those skilled in the art based on the following examination and study, or can be taught from the practice of the present invention. The objectives and other advantages of the present invention can be realized and obtained through the following description. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention will be described in detail below in conjunction with the accompanying drawings, wherein:

[0035] Figure 1 The results of the photocatalytic degradation of toluene by the composite photocatalyst obtained in Example 1 are shown.

[0036] Figure 2 These are the results of five cycles of stability testing of the composite photocatalyst obtained in Example 1 and tin dioxide.

[0037] Figure 3 This is the XRD characterization diagram of the composite photocatalyst obtained in Example 1 for toluene.

[0038] Figure 4 It is the technical roadmap of the present invention.

[0039] Figure 5 The photocatalytic degradation results of toluene by the composite photocatalyst obtained in Example 2 are shown.

[0040] Figure 6 The photocatalytic degradation results of toluene by the composite photocatalyst obtained in Example 3 are shown.

[0041] Figure 7This is a comparative example 1 of the catalytic activity experiment of doping tin dioxide with different metal materials or non-metal materials.

[0042] Figure 8 The composite material obtained in Comparative Example 2 was subjected to a photocatalytic degradation experiment of toluene.

[0043] Fig. 9 This is an experiment on removing pollutants in water using the composite photocatalyst obtained in Example 1. DETAILED DESCRIPTION

[0044] The present invention will be further described below in conjunction with specific implementation modes.

[0045] Embodiment 1:

[0046] like Figure 4 As shown, a method for preparing a composite photocatalyst, the specific steps are as follows:

[0047] (1) grinding 50 g of magnesium slag to less than 150 μm, adding 150 mL of dilute sulfuric acid with a mass concentration of 20%, acid leaching for 24 h, filtering out the filter residue, and obtaining a leachate containing magnesium sulfate;

[0048] (2) adding 300 mL of 28% ammonia water to the leaching solution obtained in step 1, stirring the mixture under magnetic force at 25° C. for 30 min, and filtering the mixture to obtain a filter residue containing Mg(OH)2;

[0049] (3) Add 15% diluted HNO3 dropwise to the filter residue obtained in step (2) to make the pH of the solution about 5. After the precipitate disappears, the supernatant is the Mg(NO3)2 solution, which is diluted with distilled water to make the Mg(NO3)2 solution 2+ =0.5mol / L;

[0050] (4) Prepare SnCl4·5H2O at 0.5 mol / L and urea (CH4N2O) at 3 mol / L;

[0051] (5) Add 100 mL of distilled water to a 200 mL hydrothermal kettle and mix the above Mg(NO3)2 solution with SnCl4·5H2O solution to make n(Mg 2+ ): n(Sn 4+ ) were 1:4 (4.8mL, 19.2mL), 1:3 (6mL, 18mL), 1:2 (8mL, 16mL), 1:1 (12mL, 12mL), 2:1 (16mL, 8mL), 3:1 (18mL, 6mL), 4:1 (19.2mL, 4.8mL), respectively denoted as MS1:4, MS1:3, MS1:2, MS1:1, MS2:1, MS 3:1, MS 4:1, and Mg 2+ With Sn4+ The total volume of the solutions was 24 mL; the other two groups only added 24 mL of Mg(NO3)2 and SnCl4·5H2O, which were recorded as M and S, respectively;

[0052] (6) adding 12 mL of urea solution to the mixed solution obtained in step (5);

[0053] (7) After stirring for 10 min, the mixture was placed in an oven at 120 °C and subjected to hydrothermal reaction for 12 h;

[0054] (8) After the reaction, the sample was washed with distilled water and centrifuged three times, and washed with 95% ethanol solution and centrifuged once. The sample was placed in an oven and dried at 60°C for 12 hours, and then ground to obtain a Mg / SnO2 catalyst.

[0055] Embodiment 2:

[0056] like Figure 4 As shown, a method for preparing a composite photocatalyst, the specific steps are as follows:

[0057] The chemical waste liquid containing Mg(NO3)2 is passed through a semipermeable membrane to separate the solute and solvent in the waste liquid, and the solvent is recovered and diluted to a concentration of 0.05mol / L; at the same time, the chemical waste liquid containing MgCl2 is passed through a semipermeable membrane to separate the solute and solvent in the same manner, and the solvent is recovered and diluted to a concentration of 0.05mol / L. Take MgCl2 and Mg(NO3)2 with volumes of 40mL and 20mL (MMS-1), 30mL and 30mL (MMS-2), 20mL and 40mL (MMS-3) respectively, add 30mL of 0.05mol / L SnCl4·5H2O solution, then add 45mL of 4mol / L urea, stir for 10min, transfer to a 200mL hydrothermal autoclave, place in an oven at 120℃ to react for 12h, wash with distilled water and centrifuge 3 times, wash with 95% volume concentration ethanol solution and centrifuge once, dry at 60℃ for 12h, grind, and record as MMS-1, MMS-2 and MMS-3.

[0058] Embodiment 3:

[0059] Prepare 0.1mol / L Mg(NO3)2·9H2O solution, SnCl4·5H2O solution and urea solution respectively. Take 10mL of Mg(NO3)2·9H2O solution and 5mL of SnCl4·5H2O solution and add them to the inner lining of 5 100mL hydrothermal kettles, stir evenly, then add 30, 37.5, 45, 52.5, and 60mL of urea solution respectively, add distilled water to make the total volume of the reaction solution 80mL, stir at 500rpm for 10min to make the solution evenly mixed. Cover the hydrothermal kettle and put it in an oven, react at 120℃ for 12 hours, centrifuge the sample after reaction 3 times with distilled water, and then centrifuge it once with 95% ethanol solution by volume concentration. Dry in a 60℃ oven for 12 hours and grind. The samples are recorded as: MS-1, MS-2, MS-3, MS-4 and MS-5.

[0060] Comparative Example 1

[0061] Doping of tin dioxide with different metal materials or non-metal materials

[0062] Add 100 mL of distilled water to a 200 mL hydrothermal kettle, then add 24 mL of 0.5 mol / L tin tetrachloride solution, then add 6 mmol of doping reagent, and finally add 12 mL of 3 mol / L urea. Hydrothermally react at 120 ° C for 12 hours. After cooling to room temperature, wash with distilled water 3 times, wash once with 95% volume concentration ethanol solution, dry at 60 ° C for 12 hours, and grind.

[0063] The doping agents are sodium fluoride, boric acid, molybdenum chloride, ammonium fluoride, silicic acid, barium nitrate, calcium chloride, sodium sulfide, bismuth nitrate, aluminum oxide, tantalum chloride and magnesium nitrate.

[0064] Comparative Example 2

[0065] Reference (Vadivel S, Rajarajan G. Effect of Mg doping on structural, optical and photocatalytic activity of SnO2 nanostructure thin films[J]. Journal of Materials Science Materials in Electronics, 2015, 26(8): 1-8. DOI: 10.1007 / s10854-015-3154-5.) A magnesium-doped tin dioxide nanostructure film was prepared, and composite materials with doping ratios of 5wt%, 10wt%, and 15wt% were synthesized.

[0066] Test example

[0067] 1. Photocatalytic degradation of VOCs experiment

[0068] The composite photocatalyst obtained in Example 1, Example 2 or Example 3 is used to photocatalytically degrade VOCs, taking typical VOCs toluene as an example. Take 0.2g of the composite photocatalyst, moisten it with ethanol and evenly apply it on a frosted glass sheet, and put it in an oven for one minute to evaporate the excess ethanol. Then put the prepared sample into the reaction chamber for reaction (the volume of the rectangular continuous flow reaction chamber is 0.34L, i.e. 200mm×100mm×17mm);

[0069] The toluene concentration was 70 ppm, the equilibrium time was 7.5 min, and then the light was turned on for photocatalytic reaction, and the reaction time was 1 h. Figure 1 The removal effect of the composite photocatalyst obtained in Example 1 at different Mg / SnO2 ratios was more than 80%. When Mg / Sn=2:1, the catalytic degradation rate reached 96%. Figure 1 However, SnCl4·5H2O was not added during the preparation process, that is, the magnesium salt product had no effect on removing toluene; and when Mg(NO3)2 (i.e., SnO2 sample) was not added during the preparation process, the catalytic effect was poor, and after a period of catalysis (about 30 minutes), the catalyst gradually deactivated and the catalytic effect became poor. Figure 2 It can be seen that after five cyclic stability experiments were conducted on Mg-SnO2 and SnO2, it can be clearly found that the removal effect of Mg-SnO2 on toluene still maintains a very high catalytic effect (photocatalytic removal rate is 96%) and stability (the sample maintains a very high catalytic activity after 5 cycle experiments); while the removal effect of SnO2 decreases after each cycle, and the catalytic removal rate is only about 10% after five cycles.

[0070] The samples in Example 1 were subjected to XRD test. Figure 3 The results show that the diffraction peak of SnO2 can be detected in all samples. The Mg peak is not detected at low doping ratios because the doping ratio of Mg is small. By calculating the lattice spacing through the Bragg equation, it is found that Mg exists in the form of substitution doping. When the doping amount of Mg increases, such as Mg / SnO2=3:1, 4:1, the peak of magnesium salt appears.

[0071] The technical roadmap of the present invention is as follows Figure 4 As shown, waste is prepared into a simple and highly active composite photocatalyst through resource utilization.

[0072] Similarly, the photocatalytic performance of the composite photocatalyst obtained in Example 2 was tested. The toluene concentration was 70ppm, the amount of catalyst was 0.2g, and it was placed in the reaction chamber for a continuous flow photocatalytic effect experiment. The experimental results showed that the removal efficiency of toluene by the three catalysts under light conditions was still very good, and all maintained a removal effect of more than 80%. Figure 5 It can be seen that the changes in different anion types and concentrations have little effect on the photocatalytic effect of the composite photocatalyst, and it has a good photocatalytic removal effect on toluene.

[0073] Similarly, the photocatalytic performance of the composite photocatalyst obtained in Example 3 was tested. The toluene concentration was 70ppm, the amount of catalyst was 0.2g, and it was placed in the reaction chamber for a continuous flow photocatalytic effect experiment. The experimental results showed that the removal efficiency of toluene by the five catalysts under light conditions was still very good, and all maintained a removal effect of more than 90%. Figure 6 , it can be seen that when the molar ratio of the total molar amount of magnesium ions and tin ions to urea varies in the range of 1:2 to 4 (1:2, 1:2.5, 1:3, 1:3.5 and 1:4), all catalysts have a good photocatalytic effect on toluene.

[0074] Comparative Example 1 explored the doping of SnO2 with different metal materials and non-metal materials, and carried out a continuous flow photocatalytic reaction under the conditions of 70ppm toluene concentration and 0.2g catalyst. Compared with the catalytic effect of the original SnO2 sample, whether the catalytic activity was improved or not, deactivation occurred within 30min. However, the SnO2 doped with Mg not only did not deactivate, but also had a much better catalytic activity than the background ( Figure 7 ). It can be concluded that many non-metallic and metal doping methods do not significantly improve the activity and stability of SnO2, while Mg-doped SnO2 can solve the original deactivation problem of SnO2 catalyst and greatly improve the photocatalytic activity and stability.

[0075] The removal effect of toluene by the composite materials with different doping ratios obtained in Comparative Example 2 was tested. The results are shown in Figure 8 . For comparison under the same dosage (catalyst dosage of 0.2g, continuous flow reaction, toluene concentration of 70ppm), the removal rate of the composite photocatalyst obtained in Example 1 can reach 90% within 20 minutes, and the removal rate of one hour can reach 96%, and the removal rate is not affected by five cycles. The removal effect of the composite material obtained in Comparative Example 2 under different ratio conditions is only about 2-3% in one hour.

[0076] 2. Catalytic removal of common pollutants in water, such as chemical oxygen demand (COD) and ammonia nitrogen (measured in N)

[0077] The experimental sewage was diluted by the influent of the actual sewage plant. The initial concentration of COD was 122mg / L, and the initial concentration of ammonia nitrogen was 15.97mg / L. The sewage volume was 500mL, the dosage of the catalyst was 1g, and the photocatalytic time was 30min. The concentration of COD after the reaction was 93mg / L (background removal rate 23%) and 21mg / L (removal rate of the sample after doping was 82.79%). The concentration of ammonia nitrogen after the reaction was 9.27mg / L (background removal rate 41.92%) and 2.42mg / L (removal rate of the sample after doping was 84.48%).

[0078] ( Fig. 9 )

[0079] The composite photocatalyst obtained in Example 1 can promote the degradation of pollutants through photocatalysis, and has a significant removal effect on COD and ammonia nitrogen in sewage, and the effluent meets the national Class A effluent standard. This provides technical support for the practical application of photocatalysis in sewage treatment plants, which is of great significance for improving the urban environment and promoting sustainable development. (In the national Class A effluent standard, the chemical oxygen demand (COD) should be ≤50mg / L, and the ammonia nitrogen (in terms of N) should be ≤5mg / L.)

[0080] Therefore, the composite photocatalyst obtained in Example 1 also has a significant effect on the removal of pollutants from water bodies.

[0081] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution, which should be included in the scope of the claims of the present invention.

Claims

1. A method for preparing a composite photocatalyst by recycling magnesium slag or waste liquid, characterized in that: The specific steps are as follows: S1. Pretreating the magnesium slag or waste liquid to obtain a magnesium salt solution; S2. The magnesium salt solution is mixed evenly with the tin tetrachloride solution and the urea solution to obtain a mixed solution, so that the molar ratio of the total molar amount of magnesium ions and tin ions to urea is 1:2-4, and a hydrothermal reaction is performed and post-treated to obtain the composite photocatalyst.

2. The method according to claim 1, characterized in that: In step S1, the pretreatment method of the magnesium slag is as follows: the magnesium slag is ground to less than 150 μm, dried at 105° C. to constant weight, and the slag powder is then leached with a first acid solution for 24 hours, filtered, and a leachate containing magnesium sulfate is obtained. Then, a 28% ammonia solution is added to the leachate, stirred, filtered, and a filter residue containing Mg(OH)2 is obtained. Finally, a second acid solution is added dropwise to the filter residue until the pH is 4-6 and the precipitate disappears. The supernatant is taken and the magnesium ion concentration is adjusted.

3. The method according to claim 1, characterized in that In step S1, the main component of the waste liquid is Mg 2+ The corresponding pretreatment method is concentration or dilution with distilled water to adjust the magnesium ion concentration.

4. The method according to claim 1, characterized in that: In step S2, the molar ratio of the total molar amount of magnesium ions and tin ions to urea is 1:

3.

5. The method according to claim 1, characterized in that In step S2, the molar ratio of magnesium ions to tin ions is 1 to 4:

1.

6. The method according to claim 1, characterized in that In step S2, stirring is performed at 500 rpm for 10 minutes to achieve uniform mixing.

7. The method according to claim 1, characterized in that In step S2, the process conditions of the hydrothermal reaction are: hydrothermal reaction at 120° C. for 12 hours.

8. The method according to claim 1, characterized in that: In step S2, the post-treatment includes: washing with distilled water and centrifuging for 3 times, washing with 95% ethanol solution and centrifuging once, drying at 60°C for 12 hours, and grinding.

9. A composite photocatalyst prepared by the method according to any one of claims 1 to 8.

10. Use of the composite photocatalyst according to claim 9 in removing air pollutants and water pollutants.

Citation Information

Patent Citations

  • A method for magnesium resource utilization in a hydrometallurgical zinc smelting process

    CN109867463B

  • Resource utilization method of magnesium-containing wastewater generated by nickel-cobalt hydrometallurgy

    CN117023612A